Response surface methodology application in optimization of performance and exhaust emissions of RON 98, aviation gasoline 100LL and the blends in Lycoming O-320 engine. (15th November 2019) - Kumar, Thanikasalam; Mohsin, Rahmat; Majid, Zulkifli Abd; Ghafir, Mohammad Fahmi Abdul; Yusuf, Nur Kamilah; Kim, JeYoung; Wash, Ananth Manickam; Sahri, Dzulkarnain Mohd
Graphical abstract: Highlights: Performance and emissions of AVGAS, MOGAS and the blends were investigated in a SI aviation engine. Response Surface Methodology was used to optimise the performance and emission. Interaction effects between engine speed, investigated fuel and output responses were studied. The higher the concentration of AVGAS in the blend, the lower the performance and the higher the emission. Desirability of 0.713 was found to be the best solution, exhibited by RON 98 (Motor Gasoline). Abstract: AVGAS is a specially blended gasoline for use in aircraft engines of the piston type. AVGAS contains TEL additive for octane boosting but is viewed as a human cancer-causing agent. Alternatively, unleaded Motor Gasoline (MOGAS) is an alternative for AVGAS. In this study, all the test fuels were characterised based on chemical and physical properties of the fuels. GC analysis of the tested fuels were categorised based on hydrocarbon types and basic fuel properties. For optimisation, engine speed and fuel were the input parameters and Brake Horsepower (BHP), Brake Thermal Efficiency (BTHE), Brake Specific Fuel Consumption (BSFC), Carbon Monoxide (CO), Unburned Hydrocarbon (HC) and Nitrogen Oxides (NOx) were the output responses. The engine speed (RPM) was varied at 2000–2700 and the fuels were RON 98 (unleaded high-aromatic MOGAS), AVGAS, 20%, 30%, 50%, 70% and 80% blend ratios. One factor response surface methodology (RSM) which contained 49 experimental runs was used. Analysis of Variance (ANOVA) was performed on the models. Values of "Prob > F", differences between "Predicted R2" and "adjusted R2" and 'Adequate Precision" determined model validation. BHP and BTHE were maximised and BSFC and the emissions were minimised. Confirmation test was carried out to evaluate errors. Results indicated that at 2077 RPM, RON 98 fuel gave optimum solution of all tested fuels and the corresponding values of BHP, BTHE, BSFC, CO, HC and NOx were found to be 136 Hp, 31%, 0.25 Kg/kW-hr, 6.7%, 350 ppm and 51 ppm respectively with a desirability index of 0.713.